An endoparasitoid wasp influences host DNA methylation - Kumar, Sunil (Sci Rep, 2017)
Parasitism by endoparasitoid wasps changes the expression of various host genes, and alters host immune and developmental processes. However, it is not clearly understood how parasitism changes host gene expression in a whole genome scale. This study focused on an epigenetic control of Cotesia plutellae, an endoparasitoid wasp, against its host, Plutella xylostella. Two DNA methyltransferases (DNMT-1 and DNMT-2) are encoded in the genome of P. xylostella. In addition, methyl-binding domain proteins (MBDs) and DNA demethylation factor, ten-eleven translation protein (TET) are encoded. DNA methylation of P. xylostella genomic DNA was confirmed by restriction digestion with Gla I specific to 5-methylcytosine. DNA methylation intensity in parasitized (P) larvae was decreased compared to that in nonparasitized (NP) larvae, especially at late parasitic stage, at which expression levels of both DNMT-1 and DNMT-2 were also decreased. DNA demethylation of P. xylostella was confirmed in both NP and P larvae by restriction digestion with PvuRts1I recognizing 5-hydroxymethyl cytosine. Parasitism also suppressed expression levels of TET and MBDs. Treatment of 5-aza-2′-deoxycytidine (AZA) reduced DNA methylation intensity of NP larvae, causing suppression of hemocyte-spreading behavior and delay of immature development. RNA interference of DNMT-1 or DNMT-2 mimicked the adverse effects of AZA.